2005
DOI: 10.1897/04-497r.1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water chemistry on the acute toxicity of copper and zinc to the cladoceran Ceriodaphnia cf dubia

Abstract: This study determined the influence of key water chemistry parameters (pH, alkalinity, dissolved organic carbon [DOC], and hardness) on the aqueous speciation of copper and zinc and its relationship to the acute toxicity of these metals to the cladoceran Ceriodaphnia cf dubia. Immobilization tests were performed for 48-h in synthetic or natural waters buffered at various pH values from 5.5 to 8.4 (other chemical parameters held constant). The toxicity of copper to C. cf dubia decreased fivefold with increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
48
1
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 45 publications
(66 reference statements)
8
48
1
11
Order By: Relevance
“…in 24 h while, a million-fold decrease was observed for pH 7.0, with the precipitation of insoluble copper complexes observed at pH > 6.0, suggesting that pH is an important factor in determining the efficiency of copper ionization for killing Legionella species in water. Water chemistry varies with many parameters, such as pH, and a decrease in copper toxicity has been reported with an increase in pH [66]. In addition, numerous studies have been conducted to assess copper toxicity in water environments [67], and it was found to be due to free cupric ion Cu 2+ in Sunda (1975) [68].…”
Section: Resultsmentioning
confidence: 99%
“…in 24 h while, a million-fold decrease was observed for pH 7.0, with the precipitation of insoluble copper complexes observed at pH > 6.0, suggesting that pH is an important factor in determining the efficiency of copper ionization for killing Legionella species in water. Water chemistry varies with many parameters, such as pH, and a decrease in copper toxicity has been reported with an increase in pH [66]. In addition, numerous studies have been conducted to assess copper toxicity in water environments [67], and it was found to be due to free cupric ion Cu 2+ in Sunda (1975) [68].…”
Section: Resultsmentioning
confidence: 99%
“…However, only a small acceptable range exists for the appropriate doses for copper treatments (i.e., the range of doses that are safe for the fish but toxic to the algae). Moreover, the toxicity of copper in aquatic organisms is strongly influenced by complex interactions with environmental variables such as pH, water temperature, and the concentrations of calcium and dissolved organic matter (Schrader et al, 2005;Hyne et al, 2005). These complex interactions are mostly not understood, making consistency in safe and effective copper treatments for algae control almost impossible.…”
mentioning
confidence: 99%
“…Hyne et al (2005) also showed that increasing the hardness from 44 to 374 mg/L CaCO 3 decreased Zn toxicity by 57%, at a slightly more acidic pH than the study of Yim et al (2006).…”
Section: Hardness Amd Detoxificationmentioning
confidence: 71%